2022
DOI: 10.1021/acs.jctc.2c00602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Algorithm of the Divide-and-Conquer Unitary Coupled Cluster Method with a Variational Quantum Eigensolver

Abstract: The variational quantum eigensolver (VQE) with shallow or constant-depth quantum circuits is one of the most pursued approaches in the noisy intermediate-scale quantum (NISQ) devices with incoherent errors. In this study, the divide-and-conquer (DC) linear scaling technique, which divides the entire system into several fragments, is applied to the VQE algorithm based on the unitary coupled cluster (UCC) method, denoted as DC-qUCC/VQE, to reduce the number of required qubits. The unitarity of the UCC ansatz tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Research has also focused on incorporating problem decomposition techniques developed for classical quantum chemistry applications into quantum algorithms to further improve the efficiency of simulations on near-term quantum and FTQC devices. Problem decomposition techniques offer the advantage of decomposing the full electronic structure problem of a molecule into smaller subproblems that can be solved with fewer qubits and qubit gates, and the aforementioned preprocessed Hamiltonians can be easily combined. Such approaches have a long history, originating from the application of the Bethe–Goldstone equation in quantum chemistry in the 1960s. It has been shown that, by decomposing the correlation energy of the molecular system into n -body subsystems (increments) through the expansion of occupied or virtual ,, orbitals, correlation energies close to the FCI accuracy can be recovered at low values of n in an embarrassingly parallel computation.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also focused on incorporating problem decomposition techniques developed for classical quantum chemistry applications into quantum algorithms to further improve the efficiency of simulations on near-term quantum and FTQC devices. Problem decomposition techniques offer the advantage of decomposing the full electronic structure problem of a molecule into smaller subproblems that can be solved with fewer qubits and qubit gates, and the aforementioned preprocessed Hamiltonians can be easily combined. Such approaches have a long history, originating from the application of the Bethe–Goldstone equation in quantum chemistry in the 1960s. It has been shown that, by decomposing the correlation energy of the molecular system into n -body subsystems (increments) through the expansion of occupied or virtual ,, orbitals, correlation energies close to the FCI accuracy can be recovered at low values of n in an embarrassingly parallel computation.…”
Section: Introductionmentioning
confidence: 99%
“…Employing the random subspace technique in a quantum machine learning setting would parallel the various quantum circuit splitting techniques (c.f. for example [19]), and divide-and-conquer approaches, that have been utilized in the field of quantum chemistry [20] and quantum optimization [21].…”
Section: Introductionmentioning
confidence: 99%